Identificação das áreas de úmidas no município de Portão (Bacia Hidrográfica do Rio dos Sinos) através da utilização de técnicas de geoprocessamento - Mentz, Bianca (Universidade do Vale do Rio dos Sinos, 2021)
Wet ecosystems, also known as Wetlands, are extremely important to the maintenance of local biodiversity and to keep the balance of the ecosystem services provided for it. Invironmental interactions of these location do not benefit only local fauna and flora, but also all the regional community and economy. Wetlands are formed by the presence of ion Iron2+ on it soils and by complex biological and environmental characteristics, its can be located since seascapes and coastal areas until continental and artificial locations. These ecosystems are suffering constant degradations because due to its characteristics of wet soil and underbrush its are considered unproductive. Its characteristics also make it difficult to it demarcation and elaboration of a nacional inventary to identify these ecosystems. Pertinent legislations of manegement and conservation os these areas also have discrepancies, making its preservation more difficult. Due to these factors and added to the difficult of conduct in loco studies on these ecosystems that, in mostly times, are located in hard access areas, in last years were desenvolved identificstion and monitoring studies of the wetlands by using geoprocessing tecniques that proved to be efficient tools on these kind of area. Thus, the objectives of this paper are: 1) identify wetlands on the county of Portão (RS), integrant of Rio dos Sinos Hydrographic Basin, by the supervisioned classification of satellite images and geoprocessing tools and 2) identify Iron2+ presence on these areas soil by in loco analises and use of Iron2+ indicator solution. As results, were identify 3,7383 km² of wetlands on the county (about, 4% of total área of the city). As to the identification of wetlands using the Iron2+ indicator solution, six areas of all nine choosed to make the test, had a postive result. Through the obtained results, it was found that the need for constant and efficient monitoring of wet ecosystems is urgent, because these locals has been degraded to the detriment of agricultural and urban activities, causing a huge environmental and ecological imbalance on these ecosystems, bringing drastic consequences to local fauna, flora, community and economy.
Keywords: Áreas úmidas; Ecossistemas; Preservação; Geoprocessamento; Wetland; Ecossystems; Preservation; Geoprocessing